2021
DOI: 10.1021/acs.jmedchem.1c01559
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 1-Amino-1H-imidazole-5-carboxamide Derivatives as Highly Selective, Covalent Bruton’s Tyrosine Kinase (BTK) Inhibitors

Abstract: Bruton's tyrosine kinase (BTK) inhibitors suppressing the aberrant activation of BTK have led to a paradigm shift in the therapy of B-cell malignancies. However, there is an urgent need to discover more selective covalent BTK inhibitors owing to the off-target adverse effects of the approved inhibitor, ibrutinib. Herein, we disclose the discovery and preliminary activity studies of novel BTK inhibitors carrying 1-amino-1H-imidazole-5-carboxamide as a hinge binder. The most potent BTK inhibitor 26 demonstrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Considering that the selectivity was mainly determined by the covalent bond with Cys552, if the covalent interaction between thiol and Michael addition warhead was enhanced, FGFR4-selectivity might be increased. Although the acrylamide was the common warhead interacting with the cysteine, there were still other covalent warheads, for example, propargyl amide could improve the kinase selectivity. , Thus, when replacing the acrylamide with the propargyl amide, the selectivity index of A34 was increased to 568. Interestingly, the anti-proliferative activities against Hep-3B and Huh-7 were also better than that of BLU-554 .…”
Section: Resultsmentioning
confidence: 99%
“…Considering that the selectivity was mainly determined by the covalent bond with Cys552, if the covalent interaction between thiol and Michael addition warhead was enhanced, FGFR4-selectivity might be increased. Although the acrylamide was the common warhead interacting with the cysteine, there were still other covalent warheads, for example, propargyl amide could improve the kinase selectivity. , Thus, when replacing the acrylamide with the propargyl amide, the selectivity index of A34 was increased to 568. Interestingly, the anti-proliferative activities against Hep-3B and Huh-7 were also better than that of BLU-554 .…”
Section: Resultsmentioning
confidence: 99%
“…At a dose of 7.5 mg kg −1 for 21 consecutive days (twice daily) in female CB-17 SCID nude mice with human TMD8 tumor xenografts, a better tumor inhibition could be observed with a dose-dependent increase in drug exposure (compound 35 TGI = 96%, AUC 0−8h = 1782 ng h mL −1 , C max = 1003 ng mL −1 , compound 24 TGI = 91%); the tumor growth was completely inhibited and the tumor volume was significantly reduced at a dose of 15 mg kg −1 (TGI = 106%). 44 Given that a small portion of patients with chronic lymphocytic leukemia relapsed due to the mutation of Cys481 to Ser481 under the treatment of ibrutinib. Research had confirmed that compounds that did not covalently bind to Cys481 could be efficacious.…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%
“…At a dose of 7.5 mg kg −1 for 21 consecutive days (twice daily) in female CB-17 SCID nude mice with human TMD8 tumor xenografts, a better tumor inhibition could be observed with a dose-dependent increase in drug exposure (compound 35 TGI = 96%, AUC 0−8h = 1782 ng h mL −1 , C max = 1003 ng mL −1 , compound 24 TGI = 91%); the tumor growth was completely inhibited and the tumor volume was significantly reduced at a dose of 15 mg kg −1 (TGI = 106%). 44…”
Section: -Aminopyrazolopyrimidine Derivatives As Kinase Inhibitorsmentioning
confidence: 99%
“…Azole is a class of important heterocyclic moieties in biologically active compounds such as drugs and pesticides. Considering the importance of azoles, the application of azoles as nitrogen sources for the construction of the C–N bond via the cross-coupling reaction of C–H and N–H is a straightforward strategy for the functionalization of heterocycles. In the conventional thermochemical oxidative coupling procedures, strong oxidants or elevated temperatures are generally required. , For example, the C–H azolation of quinoxalin-2­(1 H )-ones needs a stoichiometric amount of (diacetoxy)­iodobenzene (PIDA) as an oxidant, , which generates large amounts of wastes after the reaction. On the other hand, in the recently developed photochemical or electrochemical procedures, homogeneous photocatalysts or supporting electrolytes could not be reused and recycled. In this context, we herein disclosed a simple, efficient, and recyclable heterogeneous ZnIn 2 S 4 -photocatalyzed C–H azolation reaction under visible light (456 nm) at room temperature using air as a mild oxidant.…”
Section: Introductionmentioning
confidence: 99%